Paravascular channels, cisterns, and the subarachnoid space in the rat brain: A single compartment with preferential pathways. Issue 4 (April 2017) - Bedussi, Beatrice; van der Wel, Nicole N; de Vos, Judith; van Veen, Henk; Siebes, Maria; VanBavel, Ed; Bakker, Erik NTP
Recent evidence suggests an extensive exchange of fluid and solutes between the subarachnoid space and the brain interstitium, involving preferential pathways along blood vessels. We studied the anatomical relations between brain vasculature, cerebrospinal fluid compartments, and paravascular spaces in male Wistar rats. A fluorescent tracer was infused into the cisterna magna, without affecting intracranial pressure. Tracer distribution was analyzed using a 3D imaging cryomicrotome, confocal microscopy, and correlative light and electron microscopy. We found a strong 3D colocalization of tracer with major arteries and veins in the subarachnoid space and large cisterns, attributed to relatively large subarachnoid space volumes around the vessels. Confocal imaging confirmed this colocalization and also revealed novel cisternal connections between the subarachnoid space and ventricles. Unlike the vessels in the subarachnoid space, penetrating arteries but not veins were surrounded by tracer. Correlative light and electron microscopy images indicated that this paravascular space was located outside of the endothelial layer in capillaries and just outside of the smooth muscle cells in arteries. In conclusion, the cerebrospinal fluid compartment, consisting of the subarachnoid space, cisterns, ventricles, and para-arteriolar spaces, forms a continuous and extensive network that surrounds and penetrates the rat brain, in which mixing may facilitate exchange between interstitial fluid and cerebrospinal fluid.